La modernità italiana vista dall’Europa. Un’immagine alla rovescia - Rinaldi, Niccolò (SocietàMutamentoPolitica, 2011)
Italy, indeed, falls behind in Europe in every statistics concerning with civil liberties, university education, and competitiveness and all this thanks to politicians that were not able to keep the country tight with Europe, with its idea of efficiency and modernism that, with its contradictions, Europe represents.